2021
DOI: 10.18203/2319-2003.ijbcp20211016
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effect of Nigella sativa compared with metformin on blood glucose levels in streptozotocin induced diabetic albino wistar rats

Abstract: Background: Antidiabetic drugs are many but all of them have adverse effects ranging from simple side effects to serious side effects like hypoglycemic coma. We need alternative drugs which will not only lower blood sugar level but have fewer side effects. One such daily use ingredient in our food is Nigella sativa (kalonji) which has many properties.Methods: This was an objective study in an experimental animal. We divided albino wistar rats into six groups each group with six rats. Diabetes was induced using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Another experimental animal study using streptozotocin-induced diabetic albino Wistar rats determined that the administration of 1.5 mL of N. sativa oil for 40 days produced a significant reduction of blood sugar in comparison to 100 mg/kg of metformin. 42 Similarly, an in-vitro study confirmed the antidiabetic efficacy of N. sativa flavonoids surface coated gold nanoparticles (Au-NPs), which exhibited 78% increase of antidiabetic properties. 43 …”
Section: Experimental Animal Studies Of N Sativamentioning
confidence: 82%
“…Another experimental animal study using streptozotocin-induced diabetic albino Wistar rats determined that the administration of 1.5 mL of N. sativa oil for 40 days produced a significant reduction of blood sugar in comparison to 100 mg/kg of metformin. 42 Similarly, an in-vitro study confirmed the antidiabetic efficacy of N. sativa flavonoids surface coated gold nanoparticles (Au-NPs), which exhibited 78% increase of antidiabetic properties. 43 …”
Section: Experimental Animal Studies Of N Sativamentioning
confidence: 82%
“…Both the NS volatile oil and its principal bioactive ingredient, TQ, are known to improve hyperglycemia and hyperlipidemia ( 83 ). In animal studies, NSO’s anti-hyperglycemic effect was equivalent to, if not superior to, metf, the principal hypoglycemic medicine now in use ( 155 ). Because this was a one-time trial, larger-scale research using more NS parameters may provide a clearer picture.…”
Section: The Role Of Herbal Medicine Formulations In Dm Treatmentmentioning
confidence: 99%
“…Black cumin is also known as black seed, small fennel, Roman coriander, black caraway, and black sesame (Hossain et al, 2021). The name Nigella derives from the Latin word niger, which means "black" (Sadiq et al, 2021). Although the Nigella genus contains 12 species in the Turkish flora, only N. sativa and N. damascena are cultivated in different regions of Türkiye (Can et al, 2021).…”
Section: Introductionmentioning
confidence: 99%